Two new species of Rhyacophila (Trichoptera, Rhyacophilidae) from Nepal - Kiss, Ottó (Zootaxa, 2011)
Two new species of the Rhyacophila genus (Trichoptera, Rhyacophilidae), Rhyacophila lakatosi n. sp. in the R. naviculata Group and Rhyacophila hollosii n. sp. in the R. curvata Group, from Nepal are described and illustrated with drawings of the genitalia.